MAWAR (Melawan Rentenir): Integrated MSMEs Financial Inclusion Strategy In Sharia-Based - Chasanah, Amalia Nur; Herawati, Ratna; Budiantoro, Risanda Alirasta; Sukono Putro, Febrianur Ibnu Fitroh (JEJAK: Jurnal Ekonomi dan Kebijakan, 2021)
Allah has provided Islam as life guidance to be used in taking and undergoing all life aspects, including of the management and business financing. In the perspective of Islamic finance, financing venture capital through moneylenders will makes the borrower in difficult situation. This research aims to analyze the integrated financial inclusion strategy in sharia-based MSMEs financing in the Semarang City with the MAWAR Program. Mawar program is a funding assistance program for potential micro small andÃ‚Â  medium entrepreneurs based on sharia with Murabahah by collaborating through memorandum of understanding with several other agencies, such as Sharia People Financing banks, Semarang City Amil Zakat Agency, Semarang Syariah Economic Community, Semarang City Cooperatives and Micro Enterprises Agency, telecommunications companies, branchless banking agents and financial technology institutions. The benefit obtained can provide scientific contributions to the empowerment management and can be developed into a study material for long-term planning programs by the Semarang City Government in empowering micro, small and medium enterprises so they can be competitive, independent, prosperous, and cultured based on religiosity values. The approach method used qualitative research with analytical tools is the business model canvas. Data collection method used observation, interviews, and literature study. The results of this research are with the MAWAR Program, the Semarang City Government does not charge any additional costs to the borrowers (MSMEs). The legal basis of this program is based on a memorandum of understanding between the stakeholders involved and Islamic sharia